2018
DOI: 10.31539/leea.v1i2.187
|View full text |Cite
|
Sign up to set email alerts
|

Politeness in Bad Neighbors Movie

Abstract: The research aims at describing politeness used by Americans in Bad Neighbors movie to express apology. This is a qualitative descriptive research which identified, observed, transcribed the data as well as described them in the sentences. The findings present the strategy of apologizing and the use of address terms overviewed from politeness strategies such as positive politeness, negative politeness and off record. The use of address terms in expressing apology covered terms of addressing in negative politen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…She also uses regret before stating what she has done. It is apparent that this strategy is dominant for social conflict avoidance, something very similar to the research conducted by Seli and Syafitri (2018). This strategy is also frequently exercised by those who wronged their colleagues, which is similar to the one found by Wardoyo (2017), in which he also found that when apologizing to the lecturer for coming late, students tend to use a direct apology followed by an explanation and request.…”
Section: Types Of Politeness Strategiessupporting
confidence: 76%
“…She also uses regret before stating what she has done. It is apparent that this strategy is dominant for social conflict avoidance, something very similar to the research conducted by Seli and Syafitri (2018). This strategy is also frequently exercised by those who wronged their colleagues, which is similar to the one found by Wardoyo (2017), in which he also found that when apologizing to the lecturer for coming late, students tend to use a direct apology followed by an explanation and request.…”
Section: Types Of Politeness Strategiessupporting
confidence: 76%
“…This behavior is a phenomenon that causes fear and consternation for most teachers. It takes many forms including, disruptive talking, inaudible responses, sleeping in class, tardiness and poor attendance, failure to do homework, cheating in tests and exams and willingness to speak in the target language (Seli, Syafitri, Oktaviani, 2021). Fact that disruptive behavior in the classroom is an undeniable problem faced by teachers of all generations (Abeygunawardena & Vithanapathirana, 2019).…”
Section: Introductionmentioning
confidence: 99%